Introduction: The influence of new bilateralism on southeast Asia–middle east relations and the path to deeper trans regionalism - Gürol Baba; Yew Meng Lai (Project MUSE, 2025)
Trans regionalism, characterized by flexible, non-institutional cooperation across regions, contrasts with interracialism's structured, rule-based interactions. New bilateralism, on the other hand, emerging post-Cold War, extends beyond economic governance to include strategic, security, and cultural dimensions, bypassing institutional constraints. This special issue examines the conceptual and practical complementarity of these frameworks in Middle Eastern–Southeast Asian interactions. Despite weak regional organizations and uneven intra-regional power distribution, trans regionalism and new bilateralism create adaptable, issue-specific collaboration channels. Key regional actors—Türkiye, Saudi Arabia, Iran, Malaysia, Indonesia, and Singapore—leverage these mechanisms to engage in strategic partnerships outside great-power dominance. This issue highlights the efficacy of non-institutional, pragmatic diplomacy in addressing contemporary geopolitical complexities. Case studies, such as the Indonesia-UAE and Malaysia-Saudi Arabia agreements, illustrate how these frameworks enable dynamic, sustainable cooperation. The study ultimately argues that trans regionalism and new bilateralism offer viable alternatives to formal institutions, empowering small and middle powers to navigate evolving global and regional challenges.